A framework for the implementation of the Internet of Things in Iraqi small and medium-sized enterprises - Kamosh, Yaseen Myasar Fathi (2025)
This research project aims to provide an in-depth understanding of the implementation of Internet of Things (IoT) resources by small and medium-sized enterprises (SMEs) in Iraq. On a global scale, information technology, information systems, and digital services are vital resources and represent significant shifts for SMEs' success and ability to achieve competitive advantages. Furthermore, despite the critical role of Iraqi SMEs in mitigating economic crises and spearheading successful projects, there remains a dearth of research on how these SMEs can enhance their competitive advantages, particularly in utilising IoT resources and capabilities. Existing literature examines SMEs' readiness to adopt IoT, focusing on various sectors and contexts. However, there is a lack of scholarly research in this field; researchers have yet to explore the implications of IoT use in the context of Iraqi SMEs in the information technology sector. At the same time, theoretical and empirical studies on IoT adoption and the potential for digital transformation to IoT services focus primarily on large businesses and SMEs in developed countries. Nonetheless, a gap still exists in the absence of a comprehensive framework that explains the requirements for using IoT in SMEs, the challenges that may hinder its successful implementation, or the benefits it achieves. More importantly, the areas and levels of IoT implementation in Iraqi SMEs remain unclear. In response to these limitations, this thesis contributes to the body of knowledge by integrating and elaborating on resource-based theory (RBT) and organisational information processing theory (OIPT) to explore how Iraqi SMEs implement IoT from a resource-based view to enhance their competitive advantages. Through the analysis and interpretation of the following sub-research questions: How do Iraqi SMEs evaluate their IoT implementation? What are the benefits and challenges of using IoT in Iraqi SMEs? What is an appropriate framework for IoT implementation in Iraqi SMEs? The study successfully achieves its objectives and addresses the research questions using a qualitative approach, specifically a multiple-case study strategy involving four Iraqi SMEs. Two sources, namely semi-structured interviews and documents, provide the relevant data. This research also employs thematic analysis and cross-case analysis techniques to examine the collected data. The thesis findings indicate a possibility for IoT applications in Iraqi SMEs. Furthermore, using IoT from a resource-based view significantly enhances the flexibility of the firm's internal and external activities, improves information processing and management processes, and strengthens its competitive advantages. Therefore, the key findings are presented in three sections, organised according to the research questions. Firstly, the sample case studies demonstrate a good level of technical capabilities and feasibility studies that enable them to implement IoT services in specific areas and ensure compatibility between their infrastructure and IoT devices. IoT resources successfully contribute to SME services, i.e., networks, surveillance cameras, monitoring, preventive maintenance, and intelligent customer service systems. Second, the findings from the implementation revealed that IoT capabilities are essential resources for SMEs, facilitating information analysis and enhancing both tangible and intangible resources, thus contributing to improved competitiveness. For instance, IoT increases flexibility in implementing and tracking SME activities, improves accuracy and efficiency, and provides innovative solutions. The findings identified seven prevalent sub-themes regarding the advantages of implementing IoT, including enhancing service excellence, reducing costs, improving customer satisfaction, driving company growth, strengthening the firm's reputation, supporting optimal and accurate decision-making, and fostering innovation. However, the implementation of IoT in Iraqi SMEs confronts multiple challenges that could hinder or limit its success, thereby affecting the firm's services and its customers' projects. For example, a lack of user experience and knowledge will significantly impact SMEs' plans to utilise IoT resources efficiently. Therefore, the study's results explored six sub-themes that need to be addressed, including the lack of security protection for IoT protocols, insufficient experience and knowledge in the field of IoT, the absence of government legislation, the lack of feasibility studies, the high costs of IoT devices, and the lack of compatibility. Third, the developed framework made a significant contribution to research by exploring the implementation of IoT in SMEs and drawing from empirical experiences gained through case studies. It explains the tangible "technical capabilities" of hardware, software, networks, and systems, along with personnel-based resources. Additionally, the framework explored the intangible benefits of IoT, including analytical capabilities, information processing, real-time data provision, forecasting, and decision-quality support to meet the needs of decision-makers. Moreover, the firm's reputation and growth function as intangible resources that aid in evaluating the level of implementation of the vision criteria. Based on field experiences, this thesis enriched knowledge by offering recommendations and practical guidance through the proposed framework to assist Iraqi SMEs in successfully adopting and implementing IoT. Furthermore, it contributes to the understanding of researchers and academics in this field, particularly in Iraq.